O Instituto Federal de Educação, Ciência e Tecnologia de São Paulo - campus São João da Boa Vista: a questão do ensino médio integrado - Gianelli, Juliana Gimenes (Universidade Federal de São Carlos, 2018)
This thesis is based on the Marxian and Gramscian theoretical-methodological perspective and has as object of study the Integrated High School in the São João da Boa Vista Campus of the Federal Institute of Education, Science and Technology of São Paulo. The objective is to analyze the perspectives and conceptions of students, teachers, managers and socio-pedagogical team on the pedagogical principle of the Electronic Technician and Computer Technician Courses Integrated to High School, besides identifying the concepts in institutional documents and Brazilian legislation, as also to problematize the themes resulting from the interviews with the documents investigated. This study also enable us to understand the historical unfolding of secondary education in Brazil. We start from the hypothesis that the interviewees' discourses confirm the early professionalization of the young people of the Integrated High School, with the accentuation of the issue school duality, besides distancing itself from a project that develops the integral human formation of the students. Using the Focal Group technique, twenty-one students of the fourth grade of the courses, eleven teachers, three managers and three socio-pedagogical workers participated on this study. The research also implied the collection of data in documents of the institution, as well as in educational legislation. We problematize the questions found in the interviews from three central foundations: the condition of High School student´s youth; the pedagogical coursse proposals, based on the thesis defended by Nosella (2016a); and, finally, the issue of awareness and the need for cultural elevation of the masses. The thesis is that the issue of Integrated High School Education is identified, dialectically, with the problematic school duality, configured as a multiforme and non-unitary way. The results showed that the proposal of a single model of Brazilian High School Education should be universally applied to all social classes. In view of the current political situation, and due to the Law 13.415 / 2017 (Law of Reform of Secondary Education), the purpose is to think of a change that does not extinguish the quality of courses but can also reduce the disciplines of basic education, based on general culture. The challenges presented in this research must be overcome through a constant struggle for excellence in teaching, non-compulsory vocational education and the breakdown of school dualism in the field of hegemonic struggle.
Keywords: Escola unitária; Dualidade escolar; Ensino médio integrado; Formação humana integral; Princípio pedagógico; Unitary school; School duality; Integrated high school; Integral human formation; Pedagogical principle; CIENCIAS HUMANAS::EDUCACAO